Aktivitas Biostatik Torosflavon D Dari Cassia Torosa Terhadap Beberapa Cendawan Patogen Tanaman - Harizon, Harizon (Biospecies, 2009)
This research includes isolation of flavonoid Torosflavon D from Cassia Torosa, mediaformulation for pathogenic fungi growth, regeneration of pathogenic fungi, and bioactivity test of theisolated flavonoid on some pathogenic fungi. The flavonid bioactivities tests indicate that theTorosflavon D (5ppm) only effective to inhibit the radial growth of Fusarium oxysporum fsp.Lycopersici (48.75%). Statistical test (anova) indicates that concentration of the flavonid significantlyinhibit the fungi radial growth. Duncan test proves that 5 ppm concentration of Torosflavon D 5inhibits the growth of Fusarium oxysporum fsp. Lycopersici colonies optimally.